Control-Value Appraisals, Enjoyment, and Boredom in Mathematics: A Longitudinal Latent Interaction Analysis. (December 2018) - Putwain, David W.; Pekrun, Reinhard; Nicholson, Laura J.; Symes, Wendy; Becker, Sandra; Marsh, Herbert W.
Based on the control-value theory of achievement emotions, this longitudinal study examined students' control-value appraisals as antecedents of their enjoyment and boredom in mathematics. Self-report data for appraisals and emotions were collected from 579 students in their final year of primary schooling over three waves. Data were analyzed using latent interaction structural equation modeling. Control-value appraisals predicted emotions interactively depending on which specific subjective value was paired with perceived control. Achievement value amplified the positive relation between perceived control and enjoyment, and intrinsic value reduced the negative relation between perceived control and boredom. These longitudinal findings demonstrate that control and value appraisals, and their interaction, are critically important for the development of students' enjoyment and boredom over time.